Children Infected With SARS-CoV-2 From Family Clusters - Sun, Dan; Zhu, Feng; Wang, Cheng; Wu, Jing; Liu, Jie; Chen, Xue; Liu, Zhisheng; Wu, Zubo; Lu, Xiaoxia; Ma, Jiehui; Peng, Hua; Xiao, Han (Frontiers in Pediatrics, 2020)
Background: The outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is ongoing globally. Limited data are available for children with SARS-CoV-2 infection. Methods: A retrospective case study was conducted in one designated hospital for children with SARS-CoV-2 infection in Wuhan. Results: Out of the 74 children with laboratory confirmed SARS-CoV-2 infection, the median age was 5.8 years, with no notable variation based on gender. All of children had a direct exposure to at least one family member with confirmed SARS-CoV-2 infection. Most common symptoms were cough in 41(55.4%) and fever in 38 (51.4%). 40 (54.1%) children had typical patterns of viral pneumonia on CT including ground-glass opacity and interstitial abnormalities. 17 (23.0%) children were classified as asymptomatic carriers, with neither symptoms nor radiological findings. 68 (91.9%) children recovered fully and showed negative results on RT-PCR assay by nasopharyngeal swabs during our observation period. Contrast to the negative in nasopharyngeal swab, 34% of the anal swabs showed continued positive result. The mean hospitalization days of the children discharged after full recovery was 10.0 days. Conclusion: Within the family clusters that had SARS-CoV-2 infection, children had mild or even asymptomatic illness. Although CT being highly sensitive, it should be avoided in follow-up of the disease in consideration of the radiological hazards and limited clinical benefits from mild illness in children. Furthermore, it advocated that both nasopharyngeal and anal swabs should be confirmed negative from the viral load prior to declaring fully recovery as terminating the oral-fecal transmission.Asymptomatic children with family cluster are the potentially fewer known sources of COVID-19, this therefore warrant argent reassessment of the transmission dynamics of the current outbreak.